R PROGRAMMING FOR DUMMIES - ANDRIE DE VRIES; JORIS MEYS (NEW DELHI WILEY INDIA PVT LTD JOHN WILEY & SONS INC, 2024)
"R Programming for Dummies," authored by Andrie de Vries and Joris Meys, serves as a comprehensive and accessible guide for individuals looking to venture into the world of R programming. This book is particularly tailored for beginners who have no prior programming experience, aiming to demystify the complexities of R and make it approachable for a wider audience. It is also a valuable resource for experienced programmers who are new to the R language and its specific applications in data analysis and statistics.
R LANGUAGE
COMPUTERS
Keywords: PROGRAMMING; COMPUTERS